Medication Adherence and Associated Factors for Children With Tic Disorders in Western China: A Cross-Sectional Survey - Yang, Chunsong; Qin, Wanxiang; Yu, Dan; Li, Jiayuan; Zhang, Lingli (Frontiers in Neurology, 2019)
Background: Adherence to treatment remains important for successful tic disorder (TDs) management, but no studies had previously been carried out to assess adherence or the factors that affect it in children with TDs. This study therefore aimed to explore adherence to prescribed medication among children with tic disorders and to examine the associated factors. Methods: This was a cross-sectional study in western China, where children with tic disorders were recruited consecutively in 2018. We used the eight-item Morisky Medication Adherence Scale (MMAS-8) to assess adherence. We included sociodemographic data, disease status, medication status, and family conditions as independent variables and used an ordinal logistic regression model to examine the factors affecting medication adherence. Results: A total of 204 patients were included, with a response rate of 96.2%. The majority of participants (77.5%) were male, aged 7.69 ± 2.58 years. In total, 37.7% were newly diagnosed, 46.1% were review patients, and 16.2% were recurrent patients. Only 40.7% of patients showed high adherence (MMAS-8 score, 8). Decreasing quality of life (adjusted odds ratio 0.974) and living in non-rural areas (adjusted odds ratio 2.361) were significant independent determinants of non-adherence. Conclusion: The results suggest that primary healthcare providers in pediatric clinics should focus on medication adherence counseling for children with tic disorders who have a lower quality of life and live in non-rural areas.